MASA AWAL HINGGA BERKEMBANGNYA KERAJAAN AJATAPPARENG (ABAD 14 – 18) - Muhaeminah Muhaeminah; Makmur Makmur (Pubawidya: Jurnal Penelitian dan Pengembangan Arkeologi, 2016)
Ajatappareng is the  federation of five kingdoms of Sidenreng, Suppa, Rappang, Sawitto and Alitta, This alliance was formed on the  fifteenth century AD. This Ajatappareng alliance was located on the west coastal area of South Sulawes region. The aim of this research was to tract the archaeological evidence of artefact findings at Ajatappareng Region in South Sulawesi Province. First by using the survey and inteview method and then continued by excavation at some sites. This is to explain the eksistensi of a region that revealed in a lontara manuscript. Data from the Survey and test-pit excavation on the site were then collected to be analyzed on the relative dating of the manuscript data and artifact that was found. This research result showed that archaeological value was very important in which we found many artefact and features such as ancient mosque, ancient grave, ground fortification, ancient well, arrow point, numismatics finds, dakon stone, mortar, ceramic and pottery.